Модель розподілених атак у мережах зв’язку 5G - Коляденко, Ю. Ю.; Бадеєв, В. О. (ХНУРЕ, 2023)
It is shown that the 5G network architecture is not without potential vulnerabilities from an information security point of view. The controller, as a key component in managing the entire network infrastructure, is the most vulnerable element, an attack on which can lead to critical consequences for the entire infrastructure. The main threats arising from network devices remain variations of attacks such as denial of service, controller spoofing, etc. A mathematical model of the 5G network in the form of a queuing system has been developed. The advantages of the proposed model are the possibility of timely (early) attack detection and its ability to adapt to real network parameters.
Keywords: мережа зв’язку 5G; атака у мережах зв’язку